Agents intervening against delirium in the intensive care unit (AID‐ICU) – Protocol for a randomised placebo‐controlled trial of haloperidol in patients with delirium in the ICU. Issue 10 (15th August 2019) - Andersen‐Ranberg, Nina C.; Poulsen, Lone M.; Perner, Anders; Wetterslev, Jørn; Estrup, Stine; Lange, Theis; Ebdrup, Bjørn H.; Hästbacka, Johanna; Morgan, Matthew P.G.; Citerio, Giuseppe; Zafrani, Lara; Caballero, Jesús; et al.
Abstract : Background: Delirium among patients in the intensive care unit (ICU) is a common condition associated with increased morbidity and mortality. Haloperidol is the most frequently used pharmacologic intervention, but its use is not supported by firm evidence. Therefore, we are conducting Agents Intervening against Delirium in the Intensive Care Unit (AID‐ICU) trial to assess the benefits and harms of haloperidol for the treatment of ICU‐acquired delirium. Methods: AID‐ICU is an investigator‐initiated, pragmatic, international, randomised, blinded, parallel‐group, trial allocating adult ICU patients with manifest delirium 1:1 to haloperidol or placebo. Trial participants will receive intravenous 2.5 mg haloperidol three times daily or matching placebo (isotonic saline 0.9%) if they are delirious. If needed, a maximum of 20 mg/daily haloperidol/placebo is given. An escape protocol, not including haloperidol, is part of the trial protocol. The primary outcome is days alive out of the hospital within 90 days post‐randomisation. Secondary outcomes are number of days without delirium or coma, serious adverse reactions to haloperidol, usage of escape medication, number of days alive without mechanical ventilation; mortality, health‐related quality‐of‐life and cognitive function at 1‐year follow‐up. A sample size of 1000 patients is required to detect a 7‐day improvement or worsening of the mean days alive out of the hospital, type 1 error risk of 5% and power 90%. Perspective: The AID‐ICU trial is based on gold standard methodology applied to a large sample of clinically representative patients and will provide pivotal high‐quality data on the benefits and harms of haloperidol for the treatment ICU‐acquired delirium.